RETHINKING OF LYNCH’S: A STUDY OF YOUNG PEOPLE’S PERCEPTION OF SURABAYA CITY - Rully, DAMAYANTI; Florian, KOSSAK (DIMENSI (Journal of Architecture and Built Environment), 2013)
Kevin Lynch’s concept of the image of the city has influenced many academics and practitioners around the world. However, misconceptions have arisen in applying Lynch’s concept through a superficial understanding of his five elements. The main purpose of this article is to extend meaning making behind the urban elements identification, on which Lynch had put less emphasizes. The research, on which this article is based, has been conducted in Surabaya- Indonesia with young people from a mid to high economic family background that a have high dependency on private cars. In imagining the city, they emphasize more on meaning rather than physical appearances of the elements. Meaning is driven by their daily route, social life style, and ethnic background. Lynch identified three dimensions in imagining cities, namely identity, structure and meaning, which are embedded in the urban elements. In this case study, meaning is regarded as being more important than the other two and as it represents social symbols of a specific group in the city of Surabaya.